Publishing in a Medieval monastery the view from twelfth-century Engelberg - Pohl, Benjamin 1985- (Cambridge elements, 2023)
This Element contributes to the burgeoning field of medieval publishing studies with a case study of the books produced at the Benedictine monastery of Engelberg under its celebrated twelfth-century abbot, Frowin (1143-78). Frowin was the first abbot of Engelberg whose book provision policy relied on domestic production serviced by an internal scribal workforce, and his tenure marked the first major expansion of the community's library. This Element's in-depth discussion of nearly forty colophons inscribed in the books made for this library during Frowin's transformative abbacy offers a fresh perspective on monastic publishing practice in the twelfth century by directing our view to a mode of publication that has received only limited attention in scholarship to date